Spatio-temporal variation in contrasting effects of resident vegetation on establishment, growth and reproduction of dry grassland plants: implications for seed addition experiments - Knappová, Jana; Knapp, Michal; Münzbergová, Zuzana (PLoS One, 2013)
Successful establishment of plants is limited by both biotic and abiotic conditions and their interactions. Seedling establishment is also used as a direct measure of habitat suitability, but transient changes in vegetation might provide windows of opportunity allowing plant species to colonize sites which otherwise appear unsuitable. We aimed to study spatio-temporal variability in the effects of resident vegetation on establishment, growth and reproduction of dry grassland species in abandoned arable fields representing potentially suitable habitats. Seeds were sown in disturbed (bare of vegetation and roots) and undisturbed plots in three fields abandoned in the last 20 years. To assess the effects of temporal variation on plant establishment, we initiated our experiments in two years (2007 and 2008). Seventeen out of the 35 sown species flowered within two years after sowing, while three species completely failed to become established. The vegetation in the undisturbed plots facilitated seedling establishment only in the year with low spring precipitation, and the effect did not hold for all species. In contrast, growth and flowering rate were consistently much greater in the disturbed plots, but the effect size differed between the fields and years of sowing. We show that colonization is more successful when site opening by disturbance coincide with other suitable conditions such as weather or soil characteristics. Seasonal variability involved in our study emphasizes the necessity of temporal replication of sowing experiments. Studies assessing habitat suitability by seed sowing should either involve both vegetation removal treatments and untreated plots or follow the gradient of vegetation cover. We strongly recommend following the numbers of established individuals, their sizes and reproductive success when assessing habitat suitability by seed sowing since one can gain completely different results in different phases of plant life cycle.
Keywords: Seasons; Seeds; zemědělství; semena rostlinná; druhová specificita; Flowers; Species Specificity; roční období; Poaceae; Czech Republic; lipnicovité; ekosystém; Česká republika; Ecosystem; Magnoliopsida; Soil; půda; semenáček; Seedlings; květy; Agriculture